High-resolution dripwater monitoring - Relationship between modern surface climate signals and cave environments - Holz, Philipp; Nothstein, Arno; Eiche, Elisabeth; Neumann, Thomas; Kluge, Tobias (The SAO NASA Astrophysics Data System, 2018)
To apply geochemical proxy records from speleothems for paleoclimate - reconstruction, the processes controlling their formation need to be - understood. Detailed cave monitoring allows us to study the complex - interaction between modern surface climate signals above the cave and - the processes occuring in the cave environment. This relationship was - investigated within the CheckExtrema project, where we combine specific - trace element patterns and stable isotope ratios from stalagmite - Stal-KTH-2 (Kleine Teufels Cave) and stalagmite Stal-Zoo-rez (Zoolithen - Cave) in the Franconian Alb, to identify hydrological extreme events in - the past. For a reliable interpretation of the recorded geochemical - proxies, especially with regard to the response of the different - dripsites to hydrological extreme events, a detailed monitoring program - was set up in both caves with high resolution sampling since March 2016. - Dripwater collectors with integrated automatic drip counters were - installed at two dripsites in Kleine Teufels Cave and in Zoolithen Cave, - respectively. Furthermore, a rain water collector was installed above - Zoolithen Cave. Drip- and rainwater in Zoolithen Cave were sampled - weekly while dripwater in Kleine Teufels Cave was sampled at intervals - of up to two weeks. Concentrations of major and trace elements together - with δ18O and δD values were analysed at the Institute of - Applied Geosciences (AGW, KIT). Additionally, physico-chemical - parameters and alkalinity were measured onsite during 12 different cave - trips. The four dripsites show three different types of discharge - behaviour, including a slow seasonal pattern with moderate driprate - variations, a fast seasonal pattern with distinctive driprate variations - and a non-seasonal pattern. The driprate patterns of all dripsites are - mostly consistent with the main precipitation events, taking into - account a delay of several hours. The dominant cation in the dripwater - is Ca2+, which co-varies with HCO3- concentration and mostly with - driprate. Prior Calcite Precipitation (PCP) was also identified. - Distinctive peaks of trace elements, e.g. Fe, Zn and P co-vary with - times of increasing driprates, representing particles, colloids and - organic material from the surface, flushed into the cave due to heavy - precipitation events. The δ18O and δD values of the rain - water show significant variations with a trend towards lower values in - winter. In the dripwater, however, the δ18O and δD - variations are clearly damped, indicating the importance of mixing - processes in the karst aquifer. From these monitoring results we can - conclude that even seasonal trends are detectable through certain trace - elements at all types of dripsites, whereas short-term variations in - δ18O and δD values are difficult to see. Therefore, extreme - events should be preserved more clearly in the stalagmite record. Our - study emphasizes the importance of high-resolution monitoring programs - as a basis to understand cave dynamics and to interpret paleoclimatic - signals recorded in speleothems of a specific site.